Assessing Interpersonal And Intrapersonal Competencies In 8th Grade English Classes - Dharmahutama, Dharmahutama; Darmahusni, Darmahusni; Drivoka Sulistyaningrum, Siti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Interpersonal and intrapersonal competencies, which include effective Communication, collaboration, adaptability, and self-direction, have emerged as crucial skills for students to thrive in a rapidly changing world. Both competencies inseparably contribute to students' emotional intelligence and ability to communicate their needs, goals, and ideas to others in an effective way. The study was conducted at 8th grade English classes in Lampung, Indonesia. This study aimed to analyze the use of interpersonal and intrapersonal competencies in the existing assessment instruments. This research employed a needs analysis approach. The data sources are assessment instruments that refer to words, phrases, and sentences containing interpersonal and intrapersonal competencies in assessment instruments of 8th grade English classes and syllabi. The result of the existing assessment instrument components uses interpersonal and intrapersonal indicators on their components, such as Communication and selfdirection, except for collaboration and adaptability aspects, which are not included. Even though collaboration is a process of working together to achieve learning objectives that result in improved learning outcomes. The study suggested enhancing the assessment instruments to capture better and evaluate these competencies. Recommendations include revising the assessment components and incorporating additional indicators promoting collaboration and adaptability.